Autoridade e autoritarismo em Max Horkheimer - SILVA, Francivone Rodrigues da (Universidade Federal do Pará, 2014)
This dissertation focuses on the analysis of the study by Max Horkheimer on the problem of authority and authoritarianism in this essay Authority and Family from 1936. The constant presence of this phenomenon in social life is treated by Horkheimer within a dialectical and overall view of the history of Western society. The vision of the Frankfurter thinker has strong influence of the thought of Hegel, Marx and Freud in understanding the relationship between individual and society. To further elucidate these concepts, it was necessary a study on the economic issue as a strong link in human relationships as well as a study on the coercive character inherent in the formation of social being. The awareness of the presence of authority and authoritarian character is a requirement that leads human being to learn to face them, as they will never be extinguished.